RANCANG BANGUN SISTEM PENAMPUNGAN AIR MENGGUNAKAN TANDON ATAS SECARA OTOMATIS BERBASIS MIKROKONTROLER - Rezky Setyawan; Anak Agung Ngurah Amrita; Komang Oka Saputra (Program Studi Teknik Elektro UNUD, 2021)
Water reservoirs are temporary water reservoirs, usually placed at the highest. The communityplaces or installs water reservoirs above the house by using gravity so that the water can run downswiftly. In general, to get clean water, people use PDAM services or use well water. Generally, in urbanareas, the water sources used to supply water reservoirs come from PDAMs or wells (boreholes). In theclean water storage system using an upper reservoir has several problems, such as monitoring theavailable water capacity in the borehole which cannot be known so that the pump will operate for a longtime to fill water and cause damage to the pump, due to the difficulty of monitoring and controlling. Thecondition of the upper reservoir water storage is therefore designed in this study with a prototype